Conversion from forests to pastures in the Colombian Amazon leads to differences in dead wood dynamics depending on land management practices. (15th April 2016) - Navarrete, Diego; Sitch, Stephen; Aragão, Luiz E.O.C.; Pedroni, Lucio; Duque, Alvaro
Abstract: Dead wood, composed of coarse standing and fallen woody debris (CWD), is an important carbon (C) pool in tropical forests and its accounting is needed to reduce uncertainties within the strategies to mitigate climate change by reducing deforestation and forest degradation (REDD+). To date, information on CWD stocks in tropical forests is scarce and effects of land-cover conversion and land management practices on CWD dynamics remain largely unexplored. Here we present estimates on CWD stocks in primary forests in the Colombian Amazon and their dynamics along 20 years of forest-to-pasture conversion in two sub-regions with different management practices during pasture establishment: high-grazing intensity (HG) and low-grazing intensity (LG) sub-regions. Two 20-year-old chronosequences describing the forest-to-pasture conversion were identified in both sub-regions. The line-intersect and the plot-based methods were used to estimate fallen and standing CWD stocks, respectively. Total necromass in primary forests was similar between both sub-regions (35.6 ± 5.8 Mg ha −1 in HG and 37.0 ± 7.4 Mg ha −1 in LG). An increase of ∼124% in CWD stocks followed by a reduction to values close to those at the intact forests were registered after slash-and-burn practice was implemented in both sub-regions during the first two years of forest-to-pasture conversion. Implementation of machinery after using fire in HG pastures led to a reduction of 82% in CWD stocks during the second and fifth years of pasture establishment, compared to a decrease of 41% during the same period in LG where mechanization is not implemented. Finally, average necromass 20 years after forest-to-pasture conversion decreased to 3.5 ± 1.4 Mg ha −1 in HG and 9.3 ± 3.5 Mg ha −1 in LG, representing a total reduction of between 90% and 75% in each sub-region, respectively. These results highlight the importance of low-grazing intensity management practices during ranching activities in the Colombian Amazon to reduce C emissions associated with land-cover change from forest to pasture. Highlights: We assessed the impact of land-cover change and management on the dead wood. Dead wood was pronouncedly reduced after 20 yr of forest-to-pasture conversion. However, reduction of the dead wood was higher in high-grazing intensity areas. Low-grazing intensity practices contribute to reduce C emissions after deforestation. The results contribute to better quantify C emission in support of REDD+ initiatives.